Improving the performance of winter wheat planted after grain sorghum in no-till systems - Jennings, Joshua D. (Kansas State University, 2015)
Previous research has revealed that winter wheat (Triticum aestivum L.) yields are often reduced following grain sorghum [Sorghum bicolor (L.) Moench] compared to wheat after other summer crops. The objectives of the study were to: (a) evaluate grain sorghum residue management strategies to improve the performance of a following winter wheat crop in no-till systems; (b) determine grain sorghum hybrid characteristics that facilitate planting wheat following grain sorghum, and identify winter wheat cultivars that are suitable for planting after grain sorghum; (c) evaluate effect of environment, sampling time, and grain sorghum hybrid plant pigmentation on phenolic acid concentration in sorghum residues. Experiments were conducted in environments suitable for planting winter wheat following a summer crop. Treatments for objective one were: glyphosate (pre-harvest application, post-harvest, none), residue (removed, chopped, left standing), and nitrogen (34 kg ha⁻¹ applied to residue, none). Treatments for objective two and three were grain sorghum hybrids representing three maturities (early, medium, medium-late) and two plant pigmentations (red, tan), wheat cultivars occupying significant planted acreage and having favorable performance within the region. Wheat yields increased in two environments by 217 and 630 kg ha⁻¹ when glyphosate was applied to the sorghum pre-harvest. Residue chopping or removal either had no effect or a negative effect on wheat yields compared to residue left standing. Nitrogen applied to the sorghum residue increased wheat yields in only one environment. Grain sorghum hybrid characteristics did not influence winter wheat yields in any environment, but winter wheat cultivar did influence grain yields of the winter wheat in three of the four environments. Breakdown of phenolic acids depended on environment. Results for these studies indicate that wheat yield after a grain sorghum crop can be maximized by planting a red-pigmented sorghum hybrid of an early or medium maturity, desiccating the sorghum crop with pre-harvest glyphosate if it can be applied to the sorghum roughly 45 to 50 days before a frost, and with a wheat cultivar that is well suited to no-till planting.
Keywords: Grain sorghum; Winter wheat; No-till; Cropping systems; Agronomy (0285)